2013
DOI: 10.1111/jai.12352
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationship of two fish species from Cholvar River, western Iran: Mastacembelus mastacembelus (Banks & Solander, 1794) and Glyptothorax silviae Coad, 1981

Abstract: Summary Length–weight relationships have been determined for two species, Mastacembelus mastacembelus and Glyptothorax silviae. Samples were taken in 2011 from the Cholvar River in western Iran. It is believed that the size range covered is close to a commonly known size range of each species. The length–weight relationship values of b were determined as 2.66 for M. mastacembelus and 3.045 for G. silviae. However these data are based on preserved specimens, and a correction factor for live lengths and weights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…Gumus et al (2010) referred that the regression coefficient was 2.84 for M. mastacembelus from southern Anatolia, Turkey. Gerami et al (2014) found the growth regression coefficient for 32 fish (19.8-46.5) cm total length was 2.675 from Cholvar River in the Karun river basin in Iran, which is closer to find out. Wahab (2006) pointed that the condition factor of M. mastacembelus 0.23, also lower than one.…”
Section: Gonadosomatic Indexsupporting
confidence: 68%
“…Gumus et al (2010) referred that the regression coefficient was 2.84 for M. mastacembelus from southern Anatolia, Turkey. Gerami et al (2014) found the growth regression coefficient for 32 fish (19.8-46.5) cm total length was 2.675 from Cholvar River in the Karun river basin in Iran, which is closer to find out. Wahab (2006) pointed that the condition factor of M. mastacembelus 0.23, also lower than one.…”
Section: Gonadosomatic Indexsupporting
confidence: 68%
“…Some factors such as season, salinity, temperature, sex, fish health, food availability (including special/temporal distribution) may also affect the LWRs in marine species (Froese, ; Gerami et al., ; Lim et al., ). Moreover, the choice of sampling gear may affect the size range of the specimen captured, and thus the size range of ‘ a ’ and ‘ b ’ for the estimation of the LWRs.…”
Section: Discussionmentioning
confidence: 99%
“…The age and growth of M. mastacembelus, from south-eastern Anatolia were studied by Gümüş et al (2010). Then, Gerami et al (2013) reported on LWR of M. mastacembelus from Cholvar River, western Iran, and some biological properties including LWR of M. mastacembelus were reported from the upper Euphrates River Basin in Türkiye by Çoban et al (2021). Therefore, this study aimed to provide basic data and updated information about the LWR and condition factor for M. simack in two different water basins (Tigris and Murat rivers).…”
Section: Introductionmentioning
confidence: 99%